Reconstructive surgery of difficult urethrocutaneous fistula following gender‐affirming surgery - Kazuna Matsuo; Miki Kanbe; Fumitoshi Sakamoto; Yuzuru Kamei; Shusuke Akamatsu (IJU Case Reports, 2024)
Introduction In Japan, transgender individuals have historically had limited therapeutic options, prompting many to seek gender‐affirming surgeries in private or foreign clinics because of restricted access to public hospitals. This has led to challenges for patients undergoing surgery. Case presentation A transgender man underwent surgery at a private clinic and experienced recurrent complications. Subsequent examination at another clinic and our hospital revealed limited medical records, complicating our understanding of this case. After a detailed investigation, the urethrocutaneous and urethrovaginal fistulas were identified and addressed by joint urologists and plastic surgeons, resulting in no recurrence after 1 year. Conclusion This case underscores the importance of thorough preoperative assessment with a flexible mindset, emphasizing the need to avoid being misled by inadequate records or appearances in complication management of gender‐affirming surgery. Collaborative efforts among healthcare professionals based on comprehensive evaluations lead to safer complication treatments.